2008
DOI: 10.3382/ps.2008-00182
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Ileal Digestibility of Energy, Nitrogen, and Amino Acids of Soybean Meals of Different Origin in Broilers

Abstract: The coefficient of apparent ileal digestibility (CAID) of DM, gross energy (GE), N, and amino acids (AA) of 6 soybean meal (SBM) samples were compared in 21-d-old broilers. In addition, the digestibility of DM and N of diets that contained these SBM were tested in vitro. Four of the SBM were of South American origin, had a CP content varying from 45.2 to 47.2% and a trypsin inhibitor activity (TIA) varying from 4.1 to 6.5 mg/g, and were collected from local traders. The other 2 SBM were from US origin; one was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 58 publications
8
27
0
4
Order By: Relevance
“…The feed compound industry principally assumes that the digestible AA content of SBM per unit of protein is constant; disrespecting that variability may occur due to e.g. genotype, origin, processing and storage conditions [8][9][10]. The variability in SBMs has been nicely demonstrated by de Coca-Sinova et al [10] who evaluated six SBMs from different origins and found considerable variation in the chemical composition and protein quality which translated into differences in AA digestibility in broilers, so that SBM with higher levels of CP and lower levels of trypsin inhibitor activity showed higher AA digestibility.…”
Section: Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The feed compound industry principally assumes that the digestible AA content of SBM per unit of protein is constant; disrespecting that variability may occur due to e.g. genotype, origin, processing and storage conditions [8][9][10]. The variability in SBMs has been nicely demonstrated by de Coca-Sinova et al [10] who evaluated six SBMs from different origins and found considerable variation in the chemical composition and protein quality which translated into differences in AA digestibility in broilers, so that SBM with higher levels of CP and lower levels of trypsin inhibitor activity showed higher AA digestibility.…”
Section: Proteinmentioning
confidence: 99%
“…The apparent ileal digestibility (AID) of CP in SBM is typically around 80-85 %, but lower values have also been reported. In an investigation of 6 different SBMs originating from South America, US and Spain the AID of CP and AA was shown to vary considerably between the batches with the US SBM having the highest digestibility value (82.3 %) followed closely by the Spanish SBM (81.8 %) and with the South American SBM's having considerably lower (75.2-76.8 %) digestibility values [10]. These results serve to demonstrate the impact of differences in SBM quality when formulating diets to achieve the necessary protein content and AA availability.…”
Section: Protein Degrading Enzymesmentioning
confidence: 99%
“…Trypsin inhibitors, which reduce the digestibility of crude protein and amino acids, are the most anti-nutritional components of soybean meal [1,2]. They can be denatured by heat treatment, and several studies have investigated the effect of such treatment on the trypsin inhibitor activity (TIA) of soybean meal [3], or that of soybean meal TIA on the growth of livestock [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the United States department of agriculture (USDA) corn grading system and Chinese grading system are based primarily on physical characteristics, such as bulk weight. Therefore, corn is priced with disregard to variations in chemical quality due to the vast scale of analysis that would be required commercially [6] and the acceptance that nutrient value of feed ingredients may be constant based on broad-based quality designations [7]. …”
Section: Introductionmentioning
confidence: 99%